Wild bears, real bears and zoo bears: Authenticity and nature in Anthropocene tourism. (December 2022) - Bueddefeld, Jill NH; Erickson, Bruce
Within nature-based tourism research, authenticity has received a great deal of attention in relation to existential authenticity and in examining the authenticity of experiences. Yet very little research exists that explores the ways in which tourists perceive wildlife as more or less authentic, as objects in nature-based tourism discourses. This qualitative case study research explores visitors' perspectives in relation to polar bear tourism in Churchill, Manitoba (in situ) and at the Assiniboine Park Zoo's 'Journey to Churchill' exhibit (ex situ) in Winnipeg, Manitoba. The 'Journey to Churchill' exhibit was built with the intention of representing aspects of the landscape, wildlife and town-site found in and around Churchill, Manitoba. These two sites provide a unique opportunity to compare in situ and ex situ nature-based tourism experiences, since the sites have similar elements such as wildlife species, landscape features and other contextual factors (such as environmental issues and cultural influence). The findings from this research suggests that perceived authenticity of the polar bears, more than the experience, contributes to the construction of learning experiences about climate change. We review the work of authenticity in nature-based tourism and suggest a rethinking of the work of authenticity for both educators and operators in nature tourism. This research has important implications for better understanding how visitors construct their perceptions of authenticity of wildlife and the implications for the ways in which wildlife tourism experiences and authenticity narratives are constructed in Anthropocene tourism.